2022
DOI: 10.1101/2022.02.25.481990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular deconstruction of inflamed synovium defines diverse inflammatory phenotypes in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a prototypical autoimmune disease that causes destructive tissue inflammation in joints and elsewhere. Clinical challenges in RA include the empirical selection of drugs to treat patients, inadequate responders with incomplete disease remission, and lack of a cure. We profiled the full spectrum of cells in inflamed synovium from patients with RA with the goal of deconstructing the cell states and pathways characterizing pathogenic heterogeneity in RA. Our multicenter consortium eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 114 publications
4
68
0
Order By: Relevance
“…We need to better understand the molecular mechanisms that underlie these early phases of disease such that intervention could prevent either transition from pre-RA to early RA, or early RA to established disease. Ultimately, this raises the idea of precision medicine whereby molecular signatures of early disease would facilitate earlier diagnosis and identify optimal therapeutic targets8 9 that can deliver remission or immune diversion potentially at a very early stage. This is consistent with the notion of prevention of tissue damage and long term will reduce the tissue reparative burden.…”
Section: Resultsmentioning
confidence: 99%
“…We need to better understand the molecular mechanisms that underlie these early phases of disease such that intervention could prevent either transition from pre-RA to early RA, or early RA to established disease. Ultimately, this raises the idea of precision medicine whereby molecular signatures of early disease would facilitate earlier diagnosis and identify optimal therapeutic targets8 9 that can deliver remission or immune diversion potentially at a very early stage. This is consistent with the notion of prevention of tissue damage and long term will reduce the tissue reparative burden.…”
Section: Resultsmentioning
confidence: 99%
“…The future studies involving larger stratified patient cohorts will be essential to link synovial cell composition to variation in therapeutic response. Furthermore, such studies might contribute to the cell subtype-based and molecular pathway-based patient stratification across and within different clinical types of inflammatory arthritis 85 .…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal data integrations provide additional biological perspectives, through the combination of proteomics (CITE-seq), epigenetics (multiome), or spatial locations (ST), in addition to transcriptomics, which can reveal novel immunological or disease-driven insights. A very recent study with a collaborative effort from AMP (Accelerating Medicines Partnership) RA/SLE network used CITE-seq to reveal 10 distinct stromal populations and emphasized which of these populations are expanded in a particular patient group ( 35 ). Using three-dimensional spatial transcriptomics, Vickovic et al.…”
Section: Fibroblasts Play Important Roles In Different Inflammatory D...mentioning
confidence: 99%
“…demonstrated that in-depth stratification of RA synovial biopsies based on single-cell multimodal integrative analysis combined with covarying neighborhood analysis can associate cellular heterogeneity to stratified RA synovial phenotypes. Specifically, RA synovial heterogeneity was classified into six distinct subgroups or “cell type abundance phenotypes” (CTAPs) based on major cell-type abundance ( 35 ): 1) endothelial, fibroblast, and myeloid cells, 2) fibroblasts, 3) T cells and fibroblasts, 4) T and B cells, 5) T and myeloid cells, and 6) myeloid cells. Three of the CTAPs have associations with fibroblast and their immune interaction abundances suggesting that different patients, even with the same disease, have different tissue phenotypes at the core of their pathology, and accordingly, different molecules to be targeted for therapy.…”
Section: Future Directionsmentioning
confidence: 99%